2001
DOI: 10.1002/jbm.10030
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of porous biodegradable polymer scaffolds using a solvent merging/particulate leaching method

Abstract: This study developed a solvent merging/particulate leaching method for preparing three-dimensional porous scaffolds. Poly(L-lactic-co-glycolic acid) (PLGA) and sodium chloride particles were dry-mixed and cast into a special mold, through which a liquid could pass due to a pressure difference. An organic solvent was then poured into the mold to dissolve and merge the PLGA particles under negative pressure. A nonsolvent was conducted into the PLGA/salt composite to solidify and precipitate the merged PLGA matri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
146
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(147 citation statements)
references
References 32 publications
1
146
0
Order By: Relevance
“…At each time point (7,14,21, and 28 days), the media was removed, then 300 μl of fresh media and 60 μl of the MTS solution were added to each well and incubated at 37°C with 5 % CO 2 for 3 hours. After incubation, 300 μl of the mixture was transferred to a 48-well plate and diluted with 300 μl of DI water.…”
Section: In Vitro Studymentioning
confidence: 99%
See 1 more Smart Citation
“…At each time point (7,14,21, and 28 days), the media was removed, then 300 μl of fresh media and 60 μl of the MTS solution were added to each well and incubated at 37°C with 5 % CO 2 for 3 hours. After incubation, 300 μl of the mixture was transferred to a 48-well plate and diluted with 300 μl of DI water.…”
Section: In Vitro Studymentioning
confidence: 99%
“…Porosity and pore size depend on the porogen size [19][20][21]. While the use of porogens provides the control of pore size and porosity, interconnectivity of the pores can still be a problem [10,11,[20][21][22][23]. Heat sintering is a technique where the polymer microspheres are heated above glass transition (Tg) of polymer and held for certain period of time and then cooled down to room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, the resulting scaffolds can have well interconnected macroporous structure with limited core/skin effect [15]. Other techniques include the use of particle aggregation to create macroporous three-dimensional structures with porosity up to 35% [17][18][19] and solid freeform fabrication technique (SFF) such as 3D-printing [20], selective laser sintering [21], 3D-plotting [22], fused deposition modeling [2,23]. These techniques are time consuming and are limited to pore sizes greater than 50 mm and to porosity lower than 70%.…”
Section: Introductionmentioning
confidence: 99%
“…4(d). With reference to the results of [13,14], it is expected that the porosity and pore size can be adjusted by varying the salt-to-polymer ratio and the particle size, respectively.…”
Section: Porosities Compressive Moduli and Pore Architecturementioning
confidence: 99%
“…In order to resolve the problem, Liao et al [13] reported a method for preparing three dimensional polymeric scaffolds with controlled pore size and porosity. Poly(L-lacticcoglycolic acid) (PLGA) polymer particles were dry-mixed with salt particles and then cast into a Teflon mold.…”
Section: Introductionmentioning
confidence: 99%